2014
DOI: 10.1103/physrevb.90.085101
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of black phosphorus studied by angle-resolved photoemission spectroscopy

Abstract: Electronic structures of single crystalline black phosphorus were studied by state-of-art angleresolved photoemission spectroscopy. Through high resolution photon energy dependence measurements, the band dispersions along out-of-plane and in-plane directions are experimentally determined. The electrons were found to be more localized in the ab-plane than that is predicted in calculations. Beside the kz-dispersive bulk bands, resonant surface state is also observed in the momentum space. Our finds strongly sugg… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
56
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(59 citation statements)
references
References 34 publications
3
56
0
Order By: Relevance
“…We want to underline that we do not observe the additional surface state reported in Refs. [46,47]. Notably, these experiments used photon energies in the range of ∼100 eV.…”
Section: Angle-resolved Photoemission Measurements Of the Three-mentioning
confidence: 99%
“…We want to underline that we do not observe the additional surface state reported in Refs. [46,47]. Notably, these experiments used photon energies in the range of ∼100 eV.…”
Section: Angle-resolved Photoemission Measurements Of the Three-mentioning
confidence: 99%
“…[ 10 ] It is noteworthy that great technological demands for optical communications exist mainly in the infrared wavelength range around 1500 nm (0.8 eV). To this point, black phosphorus (BP), [ 11,12 ] a new member of the layered-material family with bandgap from 0.3 (bulk) to 1.5 eV (monolayer), [13][14][15] can bridge the gap between zero-gap graphene and relatively large bandgap TMDs for infrared photonics and optoelectronics.Because of the unique orthorhombic crystal structure, [ 16 ] BP shows tunable optical properties which are very sensitive to thickness, doping, and light polarization. [ 13,17,18 ] Unlike TMDs, Black phosphorus (BP) is a very promising material for telecommunication due to its direct bandgap and strong resonant absorption in near-infrared wavelength range.…”
mentioning
confidence: 99%
“…Previous studies have revealed a range of intriguing anisotropic behaviors of BP in terms of its optical spectrum, Raman scattering, light absorption, photo-detection, and electrical conductivity. [27][28][29][30][31][32][33][34] While these properties reported in the literature have formed a valuable basis, many applications in the optical domain demand more information regarding the wave characteristics of the interacting light with the BP medium, specifically its phase. Moreover, the manipulation of the phase retardance of light in conjunction with interferometric techniques allows us to achieve optical contrast much stronger than an intensity measurement alone could 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 3 offer, as has been demonstrated extensively in optical metrology.…”
mentioning
confidence: 99%